Studying the Dynamcis of Neuronal Membrane Using a Numerical Model - González, Marina; Granero, Marco Aurélio Santos; Baroni, Mariana Pelissari Monteiro Aguiar (Discontinuity, Nonlinearity, and Complexity, 2026)
The Hodgkin and Huxley model describes the electrophysiology of the membrane of the giant squid’s axon. This model was developed from measurements of passive and active electrical behavior of the nerve cell. The four-coupled nonlinear ordinary differential equations, which describe the model, are based on the behavior of sodium and potassium channels. The aim of this work is to study the dynamic behavior of a neuronal physiological system described by the Hodgkin-Huxley (H-H) model through the analysis and interpretation of numerical simulations.